1996
DOI: 10.3109/00016359609003538
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tooth surface conditions on enamel fluoride uptake after topical application of TiF4in vitro

Abstract: Three groups of extracted human teeth were sectioned longitudinally into experimental and control halves. The enamel surfaces of the three groups of teeth were pretreated with 37% H3PO4 for 1 min, 0.5 M NaClO3 for 2 h, or water rinsing for 10 min. The experimental halves of the three groups received an application of 1% TiF4 for 1 min and were washed with deionized water. The tooth specimens were then immersed in synthetic saliva for 24 h at 37 degrees C before sampling for measurement of fluoride uptake. An a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 8 publications
1
22
2
7
Order By: Relevance
“…22 In addition, TiF 4 has the ability to form an acid-resistant titanium dioxide surface film when in contact with the dental enamel surface. 4,9,10,11 The protective effect of the amorphous acid-resistant film might be mainly related to its ability to act as Table 2. EDS analysis of the surface of enamel blocks; chemical elements are shown according to the treatments (means ± standard deviation).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…22 In addition, TiF 4 has the ability to form an acid-resistant titanium dioxide surface film when in contact with the dental enamel surface. 4,9,10,11 The protective effect of the amorphous acid-resistant film might be mainly related to its ability to act as Table 2. EDS analysis of the surface of enamel blocks; chemical elements are shown according to the treatments (means ± standard deviation).…”
Section: Discussionmentioning
confidence: 99%
“…It has a profound ability to protect against demineralization due to the deposition of CaF 2 and formation of an acidresistant titanium dioxide (TiO 2 ) layer on the enamel. 4,9,10,11 TiF 4 solution is a promising anticaries compound, but it is unstable and presents a low pH value and, because of that, it is not well accepted for clinical use. 9 To overcome this problem, some authors tested the anticaries 6 and antierosive 12 potential of a TiF 4 varnish.…”
Section: Declaration Of Interestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is suggested that titanium interacts with organic components of the enamel surface, leading to an increased fluoride uptake by enamel. 14,17 However, Mundorff et al 14 suggested that hafnium and zirconium might be unable to form an acid-stable surface glaze. In contrast, by SEM analysis it could be shown that pretreatment of enamel surface with different polyvalent ions followed by application of acidulated phosphate fluoride lead to the formation of an amorphous coating on the enamel surface.…”
Section: Discussionmentioning
confidence: 99%
“…The electrostatic interaction between TiF 4 and acquired film proteins 36 and the presence of organic matrix on the dental surface 37 are capable of positively influencing the incorporation of fluoride by dental tissue 34 . Besides, the formation of an acid-resistant layer occurs on the dental surface 28,29,31,38 , which resembles to a glaze, and is ultrastructurally composed of numerous spherical particles 31,39 .…”
Section: Titanium Tetrafluoridementioning
confidence: 99%